The Superstar and the Followers: Intra-Firm Product Complementarity in International Trade - Björn Thor Arnarson (Lund University, School of Economics and Management, Department of Economics, 2017)
This paper investigates whether firms' exports of different products within a market are systematically interconnected. Using high-quality Swedish firm-registry data from 1997-2011, I first document that the distribution of firm export sales is skewed towards their best performing products ('superstars'). I then use a novel instrumental variable approach to identify if the 'superstar' products induce more trade of non-superstar products. I find evidence that the exports of low-ranked (non-star) products of a firm are contingent on the exports of a single superstar product to each destination. Extending the 'superstar' concept to a 'superstar core' of products strengthens this result. Hence, I find that the exports of non-star products complements the superstar(s) while conversely, the same complementarity is not found using low-ranked products as placebo-superstars. The main contributions of this paper is identifying a new, sizeable and systematic intra-firm-destination one-way demand driven complementarity between products that can explain export sales variation within a market. Ignoring this pattern of between product dependency may lead to an over-emphasis on product scope as products should not be viewed in isolation.
Keywords: F10; F13; F14; L10; L20; 330; Multi-product firms; product complementarity; intra-firm product dependence; within-destination export variation; Product Demand